2004
DOI: 10.1152/ajpheart.00897.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial comparison between wall shear stress measures and porcine arterial endothelial permeability

Abstract: A better understanding of how hemodynamic factors affect the integrity and function of the vascular endothelium is necessary to appreciate more fully how atherosclerosis is initiated and promoted. A novel technique is presented to assess the relation between fluid dynamic variables and the permeability of the endothelium to macromolecules. Fully anesthetized, domestic swine were intravenously injected with the albumin marker Evans blue dye, which was allowed to circulate for 90 min. After the animals were euth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
305
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 446 publications
(344 citation statements)
references
References 31 publications
12
305
1
6
Order By: Relevance
“…This is consistent with previous in vivo and experimental studies, which reported an inverse correlation between WSS and RT. 47,48 In the BTS, due to the unidirectional flow, there was a strong correlation between RT 1 and RT 2 , hence also between WSS and RT 2 . However, in the PA segment, there were many structures in the flow and the flow direction changed with the PDA/CS diameter.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with previous in vivo and experimental studies, which reported an inverse correlation between WSS and RT. 47,48 In the BTS, due to the unidirectional flow, there was a strong correlation between RT 1 and RT 2 , hence also between WSS and RT 2 . However, in the PA segment, there were many structures in the flow and the flow direction changed with the PDA/CS diameter.…”
Section: Discussionmentioning
confidence: 97%
“…High RRT values indicate regions of flow stagnation where endothelial dysfunction and high particle residence times are likely to be observed. 34 …”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
“…In particular regions of low Wall Shear Stress (WSS), highly oscillatory flow, and low Lumen-to-Wall Oxygen Flux (LWOF), leading to wall hypoxia, are all implicated in the initiation of IH. [5][6][7][8][9][10][11][12][13][14][15][16][17] There have been various computational studies of blood flow within AVF and Arterio-Venous Grafts (AVG). In 2003, Loth et al 18 simulated blood flow within idealized AVG and compared results with those obtained in vivo.…”
Section: Introductionmentioning
confidence: 99%